Semen Pattern of Infertile-Male Partners Attending for Infertility Treatment, Sylhet, Bangladesh - Khan, Laila Nazneen; chowdhury, Nowshafreen; Rahim, Riffat; Sweety, Kamrunnahar; Begum, Razia; Sultana, Tahera; Mustafa, Fahmida Naz (Mugda Medical College Journal, 2023)
Background: Infertility has major public health, economic, and psychosocial consequences, affecting approximately 15% - 20% of couples of reproductive ages. Male infertility can be caused by low sperm production, abnormal sperm function or blockages that prevent the delivery of sperm . Illness, injuries, chronic health problems, life style may contribute to male infertility. Objective: the aim of the study was to find the semen profile of infertile couples who attended the OPD of a tertiary hospital in Sylhet city. Methodology: This prospective longitudinal study was carried out in OPD of SOMCH, from June 2004 to December 2004. The study population was included with the criteria of the 100 male partners of the infertile couples who had tried for at least one year. The Exclusion criteria were men who had undergone a vasectomy. Each of the male partner of the infertile couples were provided-with detailed instructions regarding the method of collection of the semen. After three days of abstinence, the subjects were instructed to collect semen by masturbation in a clean, dry, wide-mouthed container provided by the laboratory. In most of the cases, semen was collected in the semen collection room within the premises of the laboratory, but those were unable to produce semen by masturbation were advised to bring the specimen to the laboratory as soon as possible after collection by coitusinteruptus. It was strictly suggested that the semen was to be brought within 2 hours at the test, sample which was brought after 2 hours was rejected. The sperm concentration was estimated by using the Makler counting chamber. Sperm morphology was assessed under light microscope by making a semen smear. The semen parameters were interpreted as normal or abnormal according to WHO (1999) semen analysis reference values. In patients with absence of sperm, semen analysis was repeated three times at four weeks interval before declaring azoospermia. Those patients with azoospermia and oligospermia also had a hormonal assay. Result: In this study, most (87%) of the semen specimens were between 2-3ml.In this study, 66% of the semen samples had a sperm count of more than 20 million/ml, 20% had 6-20 million/I, 5% had < 5 million/nil & 9 % had no sperm in their semen specimen (azoospermia). Out of 100 cases, 66% of semen specimens showed normal sperm concentration (>20 million/ml) . 34% showed low or no sperm concentration. Statistically, the proportion is highly significant (P=<0.001) In this study, the majority (74%) of male partners had pus cell in their semen specimen. In this study, most of the semen specimens (96%) liquefied within 30 minutes and 95% cases, pH of the semen specimen was between 7.2-7.4. In this study, out of 100 sample, sperm concentrations were found 0 in 9 samples (9%). Out of this 91 samples, 20.86% had 10-50% actively motile sperm, 2.18% had <10% motile sperm in their semen specimen. Out of 91 samples 21(23.04%) showed low sperm motility. The proportion is highly significant (P=<0.005). 2.18% semen specimen had <10% normal sperm morphology. The distribution of male partners according to normal sperm morphology & their sperm count is highly significant (P value<0.001) Conclusion: In conclusion, azoospermia and asthenozoospermia and infection in semen are found to be important factors associated with male infertility in our country Mugda Med Coll J. 2023; 6(1): 16-19